This one is simple since we already have the two x variables.equal. All we have to do is subtract the equations from one another to get the answer.
So i will subtract the left side by the other left side and the right side by the other right side
-8x - 8y -(-8x + 2y) = 0 -(-20)
distribute negative sign
-8x - 8y + 8x - 2y = 0 + 20
do the math
- 10y = 20
Y = -2
plug t into an equation
-8x -8 (-2) = 0
-8x + 16 = 0
-8x = -16
x = 2
answer (2, -2)
Answer:
The first one
"Only Lillie is correct" that's the right answer.
Step-by-step explanation:
64^2/3 = 16
Answer: The 3rd option
Step-by-step explanation: f(x) aka 5 is = to x aka 2+3 (2+3=5)
Plz make brainliest
The answer for the question shown above is the first option: x^2(x^2)^1/4
When you simplify the expression, you obtain the equivalent expression:
(x^10)^1/4
[(x^8)(x2)]^1/4
x^2(x^2)^1/4
Therefore, the asnwer is the option mentioned before.